The Effect of Plasma Rich in Growth Factors on Microglial Migration, Macroglial Gliosis and Proliferation, and Neuronal Survival - Noelia Ruzafa; Noelia Ruzafa; Xandra Pereiro; Xandra Pereiro; Alex Fonollosa; Alex Fonollosa; Alex Fonollosa; Javier Araiz; Javier Araiz; Arantxa Acera; Arantxa Acera; Elena Vecino; et al. (Frontiers Media S.A., 2021)
Plasma rich in growth factors (PRGF) is a subtype of platelet-rich plasma that has being employed in the clinic due to its capacity to accelerate tissue regeneration. Autologous PRGF has been used in ophthalmology to repair a range of retinal pathologies with some efficiency. In the present study, we have explored the role of PRGF and its effect on microglial motility, as well as its possible pro-inflammatory effects. Organotypic cultures from adult pig retinas were used to test the effect of the PRGF obtained from human as well as pig blood. Microglial migration, as well as gliosis, proliferation and the survival of retinal ganglion cells (RGCs) were analyzed by immunohistochemistry. The cytokines present in these PRGFs were analyzed by multiplex ELISA. In addition, we set out to determine if blocking some of the inflammatory components of PRGF alter its effect on microglial migration. In organotypic cultures, PRGF induces microglial migration to the outer nuclear layers as a sign of inflammation. This phenomenon could be due to the presence of several cytokines in PRGF that were quantified here, such as the major pro-inflammatory cytokines IL-1β, IL-6 and TNFα. Heterologous PRGF (human) and longer periods of cultured (3 days) induced more microglia migration than autologous porcine PRGF. Moreover, the migratory effect of microglia was partially mitigated by: 1) heat inactivation of the PRGF; 2) the presence of dexamethasone; or 3) anti-cytokine factors. Furthermore, PRGF seems not to affect gliosis, proliferation or RGC survival in organotypic cultures of adult porcine retinas. PRGF can trigger an inflammatory response as witnessed by the activation of microglial migration in the retina. This can be prevented by using autologous PRGF or if this is not possible due to autoimmune diseases, by mitigating its inflammatory effect. In addition, PRGF does not increase either the proliferation rate of microglial cells or the survival of neurons. We cannot discard the possible positive effect of microglial cells on retinal function. Further studies should be performed to warrant the use of PRGF on the nervous system.